Pengaruh Pendidikan Kesehatan terhadap Peningkatan Pengetahuan Remaja Putri tentang Kebersihan Alat Genetalia - Fera Nur Ramadhani; Tutik Agustini; Jama, Fatma; Yusrah Taqiyah; Wan Sulastri Emin (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2024)
Genital infection is a health problem that is often experienced by women. Every year, around 100 million women worldwide are exposed to genital infections which can cause vaginitis, cervicitis and urethritis, and trichomoniasis which can affect pregnancy. Adolescents' lack of knowledge and access to reproductive health services is important for their physical and psychosocial well-being. This study used a Pre-experimental Design with the type of design used One Group Pretest-Postest Design. The samples were taken by simple random sampling technique with a sample size of 59 young women. Data collection used an instrument in the form of a questionnaire on the knowledge of young women about genital hygiene before and after health education. The analysis uses the Wilcoxon test as a test tool with a significance level of α=0.05. The results of this study indicate that of the 59 people before being given health education, it was found that 28.0% had good knowledge, 45.8% had sufficient knowledge, and 25.4% had less knowledge, while after being given health education all female adolescents have good knowledge. The Wilcoxon test results obtained a value of p = 0.000, which means that the p value is smaller than the value (α) of 0.05. The conclusion in this study is that there is an effect of health education on increasing knowledge of young women about genital hygiene at SMA Negeri 09 Makassar, where the more often adolescents get health education about genital hygiene, the more knowledge students have about genital hygiene. For this reason, it is hoped that the school, especially the Guidance and Counseling teacher, is expected to motivate female students to improve their personal health, especially genital hygiene with a health education approach.